Interfacial reactions during soldering of Sn-Ag-Cu lead free solders on immersion silver and electroless nickel/ immersion gold surface finishes - Idris, Siti Rabiatull Aisha (2008)
In the on-going trend towards miniaturization in the electronics packaging industry, the increasing popularity of ultra fine line technologies has brought into question the physical aspects of pad topography and metallization. As the solder joints shrink in size, the thickness of the pad metallization available can be very small, thus rendering close control of the soldering process and development of intermetallic compounds at the solder joint is essential. Interfacial reactions and the structure of intermetallics at the solder/substrate interface play an important role in solder joint reliability and the present study was undertaken to investigate these interfacial reactions in order to have a better understanding on the formation of reactions and their growth. In this study, interfacial reactions between Sn-4Ag-0.5Cu and Sn-3Ag-0.5Cu solders and immersion silver (ImAg) and electroless nickel/immersion gold (ENIG) surface finishes were investigated. Emphasis is made on the effect of solder size, subsequent ageing of solder joints on the interfacial microstructures. Several techniques of materials characterization including optical, image analysis, scanning electron microscopy and energy dispersive X-ray analysis were used to examine and quantify the intermetallics in terms of composition, thickness and morphology. It was found that after soldering on ImAg only scallop-type Cu6Sn5 layer was formed and that its thickness increases with decreasing solder size. Subsequent ageing produced a second layer of Cu3Sn that forms between the Cu substrate and Cu6Sn5 layer. Growth kinetics showed that the Cu3Sn layer grew at a faster rate than the Cu6Sn5 and that Kirkendall voids were also observed within this Cu3Sn indicating that Cu diffuses much faster in the Cu3Sn than Sn in the Cu6Sn5. When soldering on ENIG finish, the reaction layer was found to consist of only one layer of (Cu, Ni)6Sn5 in the larger solders, while in the smallest solder (200 µm) both (Ni, Cu)3Sn and (Cu, Ni)6Sn5 were formed. These results reconciled well with the current theory of a critical Cu concentration determining the type of intermetallic layer that would form. The Ag content in the solder also affected the nucleation and growth of Ag3Sn plates as well as Cu-Sn intermetallic. Higher Ag containing Sn-Ag-Cu solder promoted growth of Cu6Sn5 rods and large Ag3Sn plates. Subjecting the solder joint to isothermal ageing induced thickening and coarsening of the intermetallics as well as changed in their morphologies. The results showed that the thickness of intermetallics increases with increasing the duration of ageing for both solders investigated and for all solder sphere sizes.